ANÁLISE MORFOMÉTRICA E ESPACIAL APLICADAS NA IDENTIFICAÇÃO DA SUSCETIBILIDADE A ENCHENTES EM BACIAS URBANAS DE IRATI-PR - RUDNIAK, ANDRÉIA (2017)
The floods represent one of the most active natural phenomena around the world. Urban floods in general are associated to two main causes: the high rate of urbanization (waterproofing) and the occupation of the riparian areas. Therefore, knowledge about the probable hydrological behavior within a river basin and the marking of areas prone to flood occurrence contributes to urban planning and to the minimization of eventual effects generated by this phenomenon. This work maps the susceptible areas to flooding in the urban perimeter of the city of Irati, PR, and calculates and interprets the morphometric indexes of the hydrographic basin of the main urban river of the city. For the different stages was used the Geographic Information System (GIS), specifically the SPRING software. In the mapping of susceptibility, the GIS was associated with fuzzy logic and hierarchical analysis (AHP) methodologies with data analysis performed in a LEGAL programming language. The criteria used for the assessment of flood prone areas were: altitude, slope, distance of waterways and degree of urbanization; The areas that fulfilled the criteria proposed in this study were classified and quantified later. In the morphometric characterization were obtained parameters such as drainage area, perimeter, compactness coefficient, shape factor, circularity index, among others. The parameters were calculated for the basin as a whole, as well as for the subbasin located within the urban perimeter. The results showed that 3,645 km² of the urban perimeter of the city of Irati, about 13.8% of the study area presents some degree of susceptibility to floods. The morphometric parameters indicated that only one of the six subbasins presents a tendency to a rounded shape, however four of them declined favorably to the same point and consequently to the formation of a flow peak.